Program Pendampingan Pemungutan Pajak Yayasan Keagamaan - Hanik Susilawati Muamarah; Marsono Marsono; Arifah Fibri Andriani (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2019)
This mentoring program aims to provide an understanding of the provisions of tax collection by religious foundations, such as the MRBJ Foundation managing the Great Mosque of Bintaro Jaya located in Bintaro Jaya, South Tangerang. In carrying out its activities, the MRBJ Foundation involves and makes payments to several parties, such as lecturers, doctors, and service providers. However, so far, the foundation has not fully understood the provisions regarding the tax deduction. Politeknik Keuangan Negara STAN (PKN STAN) conducts assistance to identify objects and calculate the amount of payable income tax that must be deducted or collected, which is deposit to the state treasury, up to the reporting of the Income Tax Period SPT. The results of the assistants are expected to enable the MRBJ foundation to analyze itself and carry out its obligations as a cutter/collector per the provisions of tax laws and regulations.